Forage grass management using treated cassava wastewater in Kalasin, Thailand (Asian Journal of Agriculture, 2025)
Abstract. Chinnabutr K, Poungchompu S. 2025. Forage grass management using treated cassava wastewater in Kalasin, Thailand. Asian J Agric 9: 645-652. At present, both small and large-scale farmers have been widely using forage grass production for animal feed, which can effectively reduce the cost of animal production and improve feed availability throughout the year. This study evaluates the economic benefits of using treated cassava wastewater for forage grass production in Kalasin Province, Thailand. Surveys were conducted during the 2021-2022 crop season with 90 farmers, including 50 users with treated wastewater and 40 farmers dependent on other water sources. Data was analyzed using descriptive statistics and an independent t-test. The results showed that farmers using treated wastewater obtained higher yields (36,253.882 kg/ha) and lower production costs (578.352 US$/ha) compared with non-users (25,035.751 kg/ha; 731.244 US$/ha). Net returns were also significantly higher among users (1,089.327 US$/ha or 0.030 US$/kg) than non-users (470.472 US$/ha or 0.019 US$/kg). Statistical analysis showed that yield (t = 3.19, p
Keywords: Forage grass, production costs, returns, treated water from cassava factories, wastewater